Electro-optically Q-switching performance of diode-pumped Ho:GdVO4 laser at 2.05 μm. (February 2023) - Wu, Jiaze; Ju, Youlun; Duan, Xiaoming; Yan, Renpeng; Ding, Yu; Yan, Dong; Wu, Yuechu; Dai, Tongyu; Fan, Jiawei
Highlights: An LGS electro-optically Q-switched Ho:GdVO4 laser operating at room temperature and directly pumped by LD is firstly reported. The maximum output energy of 3.25 mJ with a pulse width of 4.2 ns were achieved at PRK of 1 kHz. The peak power as high as 773.8 kW was achieved. Abstract: We proposed a Ho:GdVO4 laser operating at 2.05 µm in-band directly pumped by the 1.94 μm fiber-coupled laser diode, which electro-optically Q-switched by an LGS(La3 Ga5 SiO14 ) crystal. Adopting 1.0 at.%-doped Ho:GdVO4 crystal as the gain medium, a maximum output power of 6.5 W at 2047.9 nm with the absorbed pump power of 28 W was obtained in the continuous-wave mode, corresponding to a slope efficiency of 37.6 %. At a pulse repetition frequency of 1 kHz, the highest pulse energy of 3.25 mJ with a pulse width of 4.2 ns was achieved, corresponding to a peak power of 773.8 kW. In addition, the beam quality factor M 2 was measured to be 1.9 at the maximum output level by the 90/10 knife-edge method. TEM00 propagation has been verified by a camera. To the best of our knowledge, this is the first demonstration of high peak power electro-optically Q-switched Ho:GdVO4 laser directly pumped by the 1.94 μm laser diode.